COMPARATIVE LINGUISTICS: AIMS, TARGETS, DEVELOPMENT PROSPECTS - Buniiatova, Izabella (Studia Philologica, 2020)
This is a survey of comparative linguistics viewed as a set of the related paradigms that embrace comparative historical linguistics, aerial linguistics, linguistic typology and contrastive linguistics. The treatment of the science in question is largely based on the author’s long-standing experience deduced from research projects and from teaching it as a University professor. Placing the aforementioned paradigms under the umbrella concept “comparative linguistics” seems relevant and appropriate due to their sharing the key tool of investigation, i.e., COMPARISON, also due to their providing each other with applicable procedures and principles, as in case of two seemingly closer pairs, comparative historical and aerial areal linguistics, on the one hand, linguistic typology and contrastive linguistics, on the other hand. Key words: comparative linguistics, comparative historical linguistics, aerial areal linguistics, typological linguistics, contrastive linguistics.